Aetiological Profile and Short-Term Neurological Outcome of Haemorrhagic Stroke in Children. (1st July 2022) - Sharma, Sunil; Suthar, Renu; Dhawan, Sumeet R; Ahuja, Chirag Kamal; Bhatia, Prateek; Baranwal, Arun Kumar; Sankhyan, Naveen
ABSTRACT: Background: Haemorrhagic stroke (HS) accounts for nearly half of the paediatric strokes. The aetiology of HS in childhood is not well defined in the Indian context. Objectives: To study the aetiological profile and short-term neurological outcome of children with HS from North India. Methods: In a prospective observational study, consecutive patients >28 days to <12 years of age admitted with a diagnosis of HS were enrolled. Demography, clinical, radiological details and investigations were recorded. Short-term outcomes were assessed at three months follow-up with the Paediatric Cerebral Performance Category scale and Paediatric Stroke Outcome Measure (PSOM). Results: A total of 48 children with HS were enrolled. The median age was 6 months (1–58 months), and 33 (69%) were <2 years old. Vitamin K deficiency-related bleeding disorder (VKDB, 44%), central nervous system infections (19%), arteriovenous malformations (13%) and inherited coagulation disorders (8%) were the most common risk factors for HS. VKDB and inherited coagulation disorders were more frequent in children <2 years of age, and arteriovenous malformations were more frequent in children >2 years of age ( p = 0.001). During hospitalization, 21 (44%) children died. Older age, low Glasgow coma score (<8) at admission and paediatric intracerebral haemorrhage score ≥2 were associated with mortality at discharge ( p = <0.05). Among survivors, 15 (56%) children had neurological deficits (PSOM >0.5) at three month follow-up. Conclusion: VKDB, inherited coagulation disorders, central nervous system infections and arteriovenous malformations were the most common risk factors for HS. VKDB is the single most important preventable risk factor for HS in infants.